New tailored organic semiconductors thin films for optoelectronic applications - Pathak, Dinesh; Kumar, Sanjay; Andotra, Sonali; Thomas, Jibin; Kaur, Navneet; Kumar, Praveen; Kumar, Vaneet (European physical journal. Applied physics, 2021)
In this study, we have investigated new tailored organic semiconductor materials for optoelectronic application, such as organic solar cells. The carbon-based organic semiconductor material has promising advantages in organic thin-film form. Moreover, due to its low cost, organic thin films are suitable and cheaper than inorganic thin-film. The bandgap of organic semiconductors materials can be tuned and mostly lies between 2.0 eV and 4 eV and the optical absorption edge of organic semiconductors typically lies in between 1.7 eV and 3 eV. They can be easily tailored by modifying the carbon chain and legends and looks promising for engineering the bandgap to harness the solar spectrum. In this work, with new tailored organic semiconductors, the solution route is explored which is a low-cost processing method. (Anthracen-9-yl) methylene naphthalene-1-amine; 4-(anthracen-9-ylmethyleneamino)-1,5dimethyl-2-phenyl-1H-pyrazol-3-one and N-(anthracen-9-ylmethyl)-3, 4-dimethoxyaniline thin-films are processed by spin coating method with changing concentration such as 0.05 wt.% and 0.08 wt.%. Thin films of organic semiconductors were prepared on the glass substrate and annealed at 55 °C. The structural and optical behavior of (Anthracen-9-yl) methylene naphthalene-1-amine, 4-(anthracen-9-ylmethyleneamino)-1,5dimethyl-2-phenyl-1H-pyrazol-3-one, and N-(anthracen-9-ylmethyl)-3, 4-dimethoxyaniline organic semiconductors thin films is studied by X-ray diffraction (XRD), Scanning electron microscopy (SEM) and UV-Visible spectroscopy technique. The XRD data of the synthesized sample suggests the nano crystallinity of the organic layers. And, the SEM micrographs show the dense packing when we increase the wt.% 0.05 to 0.08. Additionally, analysis of the optical absorption measurements found that the engineered bandgap of synthesized thin films are 2.18 eV, 2.35 eV, 2.36eV, 2.52eV, and 2.65eV which suggest suitability for applications of optoelectronic devices such as solar cell. Such lightweight, eco-friendly and disposable new carbon-based materials seem to have the potential to replace other traditional hazardous heavy materials for future eco-friendly flat fast electronics.